Leukocyte apoptosis and pro-/anti-apoptotic proteins following downhill running - Park, K. -S.; Sedlock, D. A.; Navalta, J. W.; Lee, M. -G.; Kim, S. H. (European Journal of Applied Physiology, 2011)
The purposes of this study were to determine the effect of eccentric exercise-induced muscle damage on the induction of apoptosis in peripheral blood leukocytes and to investigate if the elevation in apoptotic leukocytes was mediated by changes in the concentration of anti-/pro-apoptotic proteins in circulation. Twelve moderately trained subjects performed three 40 min treadmill runs at ~70% VO2max: a level run (L) followed by two downhill runs (DH1 and DH2). Blood samples were taken at rest (PRE) and immediately (POST), 2, 24, and 48 h after each run. Data were analyzed using two-way repeated measures analysis of variance with post hoc Tukey tests. Creatine kinase (CK) activity was significantly elevated at 24 and 48 h following DH1 (P < 0.01). The proportion (%) of apoptotic leukocytes was significantly elevated at POST and 2 h following all three runs, and up to 48 h following DH1 (P < 0.01). Bax at 24-h post and Bax/Bcl-2 ratio at 24- (P < 0.01) and 48-h post (P < 0.05) following DH1 were greater than PRE (P < 0.05). An acute bout of moderate intensity downhill running altered CK activity, Bax concentration and the Bax/Bcl-2 ratio in circulating leukocytes resulting in a greater apoptotic response at 24- and 48-h post-exercise compared to level grade running or a second downhill run. Although the mechanism by which these proteins are altered by unaccustomed eccentric exercise is currently unknown, the differential response to DH1 versus L and DH2 indicates that it may be related to exercise-induced muscle damage.